The Effect of Using Zoom Towards online English Teaching And Learning Process In The Post Pandemic Era - Resdilla Pratiwi (Universitas Pahlawan Tuanku Tambusai, 2022)
This research deals with online teaching and learning process, the objective of this study is to explore the effect of Zoom use for online English teaching and learning process in the post pandemic era. The study was designed in mixed research model with combine Quantitative and Qualitative data. The data of this Study was students in the First semester in English Study Program. In the Quantitative aspect of the study, quasi experimental design, with a pretest-posttest control group was used and the data were analyzed by two factor variance analysis for mixed-measurements. The analysis indicated that both learning environments have different effect on the success of students and that supporting traditional environment by using zoom is more affective for increase of English teaching and learning process. For the qualitative aspect of the study, content analysis techniques were employed to analyze the data which were collected by open-ended question forms. The analysis shows that students developed positive opinions towards the use of Zoom in their courses. They demanded the same practice in their other courses as well. They reported that learning could also take place unconsciously and the messages which delivered directly by Zoom Virtual is more satisfied for their English learning. However, a few students have expressed adverse opinions about signal unstable in their area and excessive quotas during using this application. Finally, it is suggested that use of Zoom in education process be encouraged as a supportive technology